The Discovery Learning Method: An Islamic Religious Education Instructor's Strategy for Character Development - Nurjali Nurjali; Al Munip; Maimunah Maimunah; Iwan Aprianto (Zabags International Journal of Islamic Studies, 2024)
This study is to investigate how Islamic Religious Education instructors at SMP Negeri 24 Tanjung Jabung Timur can mold students' personalities using the Discovery Learning learning methodology. The research methodology for this study is qualitative deductive. Information about the learning of Islamic Religious Education and the development of students' character was gathered through observation, interviews, and documentation. The data collection, data condensation, data presentation, and conclusion-making based on the data obtained are among the data analysis methodologies employed in this study. According to the study's findings, the Islamic Religious Education instructors at SMP Negeri 24 Tanjung Jabung Timur employed the following strategies: 1. There were methods for planning, carrying out, and overseeing instruction. 2. The practice of reading Sholawat before taking classes. 3. Teachers invited students to participate in after-school programs. It is proposed that for students to develop their character, parents, teachers, and the administrator must work together as much as possible. It is intended that more studies concentrating on how student organization shapes student character will be conducted